Formation and Characterization of Sulfamethoxazole-Trimethoprim Cocrystal by Milling Process - Erizal Zaini, Yeyet C. Sumirtapura, Auzal Halim, Lili Fitriani, Sundani N. Soewandhi (Journal of Applied Pharmaceutical Science, 2017)
The purpose of this study was to describe and characterize co-crystal formation of sulfamethoxazole and trimethoprim. The co-crystal formation was carried out by solid state milling process. Co-crystal by solution co-crystallization and physical mixture were also prepared as a comparison. The potential co-crystalline phase was characterized by powder X-ray Diffraction (PXRD), thermal analysis differential scanning calorimetry (DSC), scanning electron microscope (SEM), and Fourier transform Infrared (FT-IR) spectroscopy. Effect of milling time on formation of co-crystal sulfamethoxazole and trimethoprim was investigated by DSC and PXRD analysis. The study showed that the milling process of sulfamethoxazole and trimethoprim in equimolar yielded the co-crystal. Intact co-crystal was obtained by solution co-crystallization with methanol. Prolongation of milling time accelerated the formation of co-crystal. Physical characterization showed that sulfamethoxazole and trimethoprim co-crystal demonstrated a unique powder X-ray diffraction, thermal and spectroscopic properties. The study concludes that the milling process induces equimolar co-crystal formation between sulfamethoxazole and trimethoprim. The transformation to co-crystalline phase is affected by milling time.
Keywords: Co-crystal, trimethoprim, sulfamethoxazole, milling process.